Attitude of Bank Employees towards The Role of English Language at Mandiri Bank - Marissa S Tupamahu; Sherly Gaspersz (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The English language plays an important role in communication in the global community. The role of English language skills in service industries is significant. It is necessary or desirable for people who work in the service business and frequently deal with foreigners, such as front-liners at banks. The aim of this study is to know the extent of Mandiri Bank employees awareness of the importance of English and the challenges that they face in the use of English in their field of work. This study used a mixed method, and the subjects of this study were the 33 employees of two branches of Mandiri Bank in Ambon, which are Mandiri Cabang Ambon Pantai Mardika and Mandiri Cabang Ambon Pattimura. Questionnaires, interviews, and reviews of documents are used to collect the data. The result of this research shows that there is a very high level of awareness of the need for English among Mandiri bank employees because it is needed in various bank functions, especially when dealing with foreign customers. Although the English language is indispensable in banks’ work, in reality, it is in contrast to the real condition in the office. The result shows the frequency of using the English language in their field of work is low, and it is becoming a challenge faced by bank employees. Insufficient or limited vocabularies, a lack of self-confidence, highly considered errors in using English, and different educational backgrounds also become problems for Mandiri bank employees.